Comparative legal analysis of agreements to avoid double taxation concluded by the Russian Federation with OECD and UN models within article 2 - Khusainova A. V. (Interactive science, 2018)
this article is devoted to the analysis of deviations of the Russian Federation's agreements on avoidance of double taxation within the framework of Article 2 with the OECD and UN model conventions. The author comes to the conclusion that many bilateral tax agreements deviate from OECD and UN models, not covering taxes on capital.
Keywords: tax law; налоговое право; финансовое право; financial law; соглашение об избежании двойного налогообложения; модель ОЭСР; модель ООН; agreements to aboid double taxation; OECD Model; UN Model